Network analysis of raw water supplies under complex water rights and exchanges: documentation for program MODSIM3 - Labadie, John W., author; Pineda, Andrew M., author; Bode, Dennis A., author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 1984)
The increasing complexity of water supply planning and management for municipalities such as Fort Collins requires use of computer models as an aid for City Staff and Water Board members. a generalized model called MODSIM3 is documented herein which allows a wide variety of water supply evaluations in a complex water rights structure that includes direct flow rights, storage rights, and water exchange possibilities with other users. MODSIM3 includes certain improvements over two earlier versions of MONSIM in being able to include both physical and accounting transfers of water for exchange purposes.
Prepared by John W. Labadie, and Andrew M. Pineda and Dennis A. Bode for the Water Utilities Department, City of Fort Collins, Colorado, in cooperation with Colorado Water Resources Research Institute, Colorado State University.
March 1984.
Keywords: Water-supply -- Computer simulation; Water-supply -- Colorado; Water rights -- Colorado